Enhanced Direct Reactive Power Control-Based Multi-Level Inverter for DFIG Wind System under Variable Speeds - Salah Tamalouzt; Youcef Belkhier; Younes Sahri; Mohit Bajaj; Nasim Ullah; Md. Shahariar Chowdhury; Teerawet Titseesang; Kuaanan Techato (My University, 2021)
A novel direct reactive power control strategy based on the three-level inverter topology (DRPC-3N) is proposed for a doubly fed induction generator (DFIG)-based wind power plant system. The robustness against parametric variations and control performances of the presented methodology are analyzed under random wind speeds, taking into account the effect of the heating of the windings as well as the saturation of the magnetic circuit. The performance indices include obtaining a sinusoidal AC-generated current with low THD and less ripples in the output. Moreover, the generator can be considered as a reactive power compensator, which allows for the controlling of the active and reactive power of the stator side connected directly to the grid side using only the rotor converter. In this study, unpredictable conduct of the wind velocity that forces the DFIG to operate through all modes of operation in a continual and successive way is considered. The received wind power is utilized to extract the optimum power by using an appropriate MPPT algorithm, and the pitch angle control is activated during the overspeed to restrict the produced active power. The simulation tests are performed under Matlab/Simulink and the presented results show the robustness and effectiveness of the new DRPC strategy with the proposed topology, which means that the performances are more sophisticated.
Keywords: Robustness; Power optimizer; Wind Turbine Control Systems